Reduced Humoral and Cellular Immune Response to Primary COVID-19 mRNA Vaccination in Kidney Transplanted Children Aged 5–11 Years - Jasmin K. Lalia; Raphael Schild; Marc Lütgehetmann; Gabor A. Dunay; Tilmann Kallinich; Robin Kobbe; Mona Massoud; Jun Oh; Leonora Pietzsch; Ulf Schulze-Sturm; Catharina Schuetz; Freya Sibbertsen; et al. (Viruses, 2023)
The situation of limited data concerning the response to COVID-19 mRNA vaccinations in immunocom-promised children hinders evidence-based recommendations. This prospective observational study investigated humoral and T cell responses after primary BNT162b2 vaccination in secondary immunocompromised and healthy children aged 5–11 years. Participants were categorized as: children after kidney transplantation (KTx, n = 9), proteinuric glomerulonephritis (GN, n = 4) and healthy children (controls, n = 8). Expression of activation-induced markers and cytokine secretion were determined to quantify the T cell response from PBMCs stimulated with peptide pools covering the spike glycoprotein of SARS-CoV-2 Wuhan Hu-1 and Omicron BA.5. Antibodies against SARS-CoV-2 spike receptor-binding domain were quantified in serum. Seroconversion was detected in 56% of KTx patients and in 100% of the GN patients and controls. Titer levels were significantly higher in GN patients and controls than in KTx patients. In Ktx patients, the humoral response increased after a third immunization. No differences in the frequency of antigen-specific CD4+ and CD8+ T cells between all groups were observed. T cells showed a predominant anti-viral capacity in their secreted cytokines; however, this capacity was reduced in KTx patients. This study provides missing evidence concerning the humoral and T cell response in immunocompromised children after COVID-19 vaccination.